PENERAPAN UPAYA DAMAI TERHADAP KASUS PELECEHAN SEKSUAL DI KEPOLISIAN SEKTOR CERENTI KUANTAN SINGINGI - Yanto, Fahmi Riau; Effendi, Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Article 2 of the Criminal Code says that "the criminal provisions in the legislation Indonesia apply to any person who commits an offense in Indonesia" so that could mean that every criminal is treated equally in the process and inspection mechanism in which through the stages of examination at the level of investigation , prosecution and finally decided by the courts. But in kenyataaan in the field often found that a criminal case should have been through the stages of examination at the level of investigation, prosecution and finally decided by the court only at the stage of investigation and ended up in the hands of investigators and was marked by the publication of Warrant Termination of Investigation (SP3) only on the basis the peace efforts and led to peace between the parties so entangled criminal cases, the law is not working as it should and does not provide a deterrent effect against perpetrators. As for the purpose of the author of this thesis, namely: first to determine the application of the peace efforts of the cases of sexual harassment in the Police Sector Cerenti Kuantan Singingi, second, to determine the constraints juridical encountered in the implementation of peace efforts by the Police against sexual harassment in the Police Sector Cerenti Kuantan Singingi.This type of research is classified as socio-juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted on the Law of the Police Sector Cerenti Kuantan Singingi, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data tertiary data collection techniques in research this is done with the interview, and literature study.From the results, it can be concluded that, first, to obtain justice, building on shared values, family, deliberation and values to other moral in society; Secondly, As for the reason to do the peace efforts of the cases of sexual abuse by the police sector Cerenti is that Cerenti people in the District is promoting customary law and uphold the name of norms and customs that exist in the area.Suggestions author of the issues examined are the First, the government should immediately make changes to the criminal law in Indonesia because it is already no longer in line with the habits and norms that exist today, the Second, the Government should also create regulations regarding the implementation of the case through peace, so as to avoid misuse and also doubts in solving the case of peace efforts, Third, people should be aware that the implementation of the tasks of Police is a matter that is very difficult and thus require cooperation between the police and the community, thus creating a harmonious relationship and provide information exchange between the police and society and a negative image of the police can be minimized.Keywords: Implementation - Peace Efforts - Sexual Harass